“MALIN KUNDANG” KARYA WISRAN HADI: SEBUAH PERBANDINGAN - Herry Nur Hidayat (Universitas Andalas, 2010)
This research is describe that a reader can produce new works. There are differences between ‘Legenda Malin Kundang’ with “Drama Malin Kundang’. Those differences shows the intertextuality. The differences indicate that there is a readers reactions, respons, and interpretations which have different backgrounds and horizon expectations.